2007
DOI: 10.1074/jbc.m610618200
|View full text |Cite|
|
Sign up to set email alerts
|

Binding of Pleomorphic Adenoma Gene-like 2 to the Tumor Necrosis Factor (TNF)-α-responsive Region of the NCF2 Promoter Regulates p67 Expression and NADPH Oxidase Activity

Abstract: NCF2, the gene encoding the NADPH oxidase cytosolic component p67phox , is up-regulated by TNF-␣, and we recently mapped a region in the NCF2 promoter that was required for this TNF-␣-dependent response. Because this TNF-␣-responsive region (TRR) lacked recognizable transcription factor binding elements, we performed studies to identify factors involved in regulating NCF2 via the TRR. Using the TRR sequence as bait in a yeast one-hybrid screen, we identified the zinc finger transcription factor Pleomorphic Ade… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
22
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 44 publications
(49 reference statements)
3
22
0
Order By: Relevance
“…In some cells, it was observed to concentrate at the perinuclear region ( Figure 3B, block arrow). A recent report also showed that PLAGL2 was in both cytosolic and nuclear fractions of leucocytes [13]. Interestingly, upon exposure to CoCl 2 , the signal of PLAGL2 became more intense in the nuclei, indicating the translocation of PLAGL2 from the cytoplasm into the nucleus (Figure 3C and D).…”
Section: Plagl2 Translocation To the Nucleus Of Cocl 2 Treated Cellssupporting
confidence: 59%
See 1 more Smart Citation
“…In some cells, it was observed to concentrate at the perinuclear region ( Figure 3B, block arrow). A recent report also showed that PLAGL2 was in both cytosolic and nuclear fractions of leucocytes [13]. Interestingly, upon exposure to CoCl 2 , the signal of PLAGL2 became more intense in the nuclei, indicating the translocation of PLAGL2 from the cytoplasm into the nucleus (Figure 3C and D).…”
Section: Plagl2 Translocation To the Nucleus Of Cocl 2 Treated Cellssupporting
confidence: 59%
“…More interestingly, PLAGL2 also modulates the promoter activation of NCF2 gene [13], which encodes p67 phox , a cytosolic protein involved in the NADPH oxidase electron transfer from NADPH to molecular oxygen. Taken together with our results that PLAGL2 responds to hypoxia and could prevent lung cells from hypoxia-induced functional and cytotoxic damages, it further raises an inevitable role of PLAGL2 in mediating the cellular response to oxidative stress.…”
Section: Discussionmentioning
confidence: 99%
“…However, the lack of LPS-mediated induction of p67phox transcripts throughout the differentiation process suggests a lack of Phox-mediated oxidative response at the transcriptional level in cells undergoing repeated stimulation with LPS. In mammals, the regulation of p67phox is delayed in maturing myeloid cells and thus is considered a rate-limiting cofactor in Phox activation [55]. Therefore, the aforementioned gradual, long-lasting and iterative onset of respiratory burst typical of macrophages upon continuous stimulation must depend on the activation of other ROS-generating enzymatic complexes, such as nitric oxide synthases (NOS).…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have demonstrated that various subunits or cofactors can be upregulated or downregulated by different stimuli such as cytokines, inflammatory factors, hormones, autocrines, paracrines, physical stress, and some drugs, which may be involved in transcriptional or posttranscriptional regulation of gene expression and translational or posttranslational regulation of proteins (12,408).…”
Section: Redox Molecules Associated With Lrsmentioning
confidence: 99%